2017
DOI: 10.3389/fmicb.2017.00731
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling of Piglets Infected with Virulent Classical Swine Fever Virus

Abstract: Classical swine fever (CSF) is a highly contagious swine infectious disease and causes significant economic losses for the pig industry worldwide. The objective of this study was to determine whether small molecule metabolites contribute to the pathogenesis of CSF. Birefly, serum metabolomics of CSFV Shimen strain-infected piglets were analyzed by ultraperformance liquid chromatography/electrospray ionization time-of-flight mass spectrometry (UPLC/ESI-Q-TOF/MS) in combination with multivariate statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Meanwhile, lactate participates in mitochondrial oxidative activity in cultured CHO cells and that LDHB localizes to the mitochondria [25,26]. We and other researchers have found that CSFV infection promoted lactate release and inhibits pyruvate release [38,39]. Based on these results, we hypothesized that LDHB may also elicit an effect on mitophagy.…”
Section: Introductionmentioning
confidence: 79%
“…Meanwhile, lactate participates in mitochondrial oxidative activity in cultured CHO cells and that LDHB localizes to the mitochondria [25,26]. We and other researchers have found that CSFV infection promoted lactate release and inhibits pyruvate release [38,39]. Based on these results, we hypothesized that LDHB may also elicit an effect on mitophagy.…”
Section: Introductionmentioning
confidence: 79%
“…Gong et al . demonstrated that cholesterol sulfate was elevated in the serum of piglets infected with swine fever virus 34 . Taken together, these observations indicate that this compound could be a marker of viral infection.…”
Section: Discussionmentioning
confidence: 98%
“…Serum contains thousands of proteins produced and released by cells and tissues, and, as a complex biological matrix, it reflects the general health status of the individual. Changes in the serum proteomic pattern were frequently observed during various pathophysiological abnormalities, such as viral, bacterial, or parasitic diseases, in certain food animal species, including pigs [20][21][22][23][24][25][26]. Therefore, farm animal serum proteomics has been developed in order to gain a deeper and more complete insight into the pathomechanism of these health disorders and to find potential biomarkers characteristic of their particular stages.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis (2-DE) has been used to create reference serum proteomic maps for both healthy adult pigs [17] and growing piglets [18,19]. Furthermore, various proteomic tools such as surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI TOF-MS); two-dimensional and two-dimensional differential gel electrophoresis (2-DE/2D-DIGE) followed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS); or liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) have also been applied to evaluate serum proteomic profiles of (1) pigs with acute liver failure [20]; (2) pigs exposed to stress factors, such as insufficient space [21]; (3) pigs suffering from low-dose LPS-induced inflammation [22]; and (4) pigs experimentally or naturally infected with classical swine fever virus [23,24], food-and-mouth disease virus [25] or porcine reproductive and respiratory syndrome virus [26]. However, the vast majority of Trichinella and trichinellosis proteomic studies focus on the immunoproteomic approach, in which immunoreactive proteins from various life stages and different parts or organs of the parasite are subjected to in-depth proteomic analysis [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%